Implantação de modelos experimentais de hiperprodução hepática de glicose para avaliação de fármacos com potencial antidiabético - Haida, Karissa Satomi (2011)
Liver glucose overproduction (LGO) contributes significantly in determining hyperglycemia associated with insulin resistance. However, experimental animal models to study potential biologically active products which promote reversibility of liver glucose overproduction are scarce. Moreover, it must be considered that in clinical practice there is only one antidiabetic drug with well established role to overcome the LGO, i.e., metformine. Therefore, it becomes necessary to develop new drugs to reduce the LGO which in turn, depends on the implementation of appropriated experimental models. Moreover, since infliximabe, a tumor necrosis factor alpha (TNF-α) antagonist, show a well established role to treat inflamatory diseases and to obtain a better glycemic control, we decided to investigate the possibilily of this agent to prevent liver glucose overproduction induced by saturated fat diet or diet enriched with sucrose. The implantation of one experimental model of LGO induced by diet and evaluate the possibility of prevention of this metabolic disorder with infliximabe. Male Swiss mice (30-35 g) were used. In the first study, the control group (C) received standard diet and the high lipid (HL) group received standard diet enriched with pork fat, in the proportion of 1,2 g/1,0 g, respectively. The HL group was subdividided in HL mice treated with intraperitoneal (i.p) infliximabe (10 μg dissolved in 100 μL of saline) twice a day and HL mice treated with i.p saline (100 μL) twice a day. After two weeks Control, HL + Saline and HL + Infliximabe groups (15 hs overnight fasting) were anesthetized with thiopental (120 mg/kg) and submitted to laparotomy. Before in situ liver perfusion, the blood was collected from cava vein for glucose evaluation. After a pre-infusion period (10 min), the gluconeogenic substrate L-alanine were dissolved in the perfusion fluid during 60 min, followed by a post-infusion period (10 min) to allow the return to basal levels. Samples of the effluent perfusion fluid were collected at 5 min intervals and the liver production of glucose, urea, pyruvate and L-lactate were evaluated. The differences in the glucose, urea, pyruvate and L-lactate production during and before the infusion of L-alanine allowed calculating the area under the curves (AUC). Thus, by using supraphysiological concentration of L-alanine (5mM) it was possible to measure the maximal capacity of the liver to produce glucose from this amino acid. In the second study, the animals which received standard diet (Control group) or standard diet plus sucrose 30% (w/v) dissolved in the water (group DES) until four weeks were compared. During this period the daily food and water ingestion were measured and the daily caloric intake were evaluated. Body weigh were measured weekly. After two, three or four weeks of treatment Control and DES groups (15 hs overnight fasting) were submitted to anesthesia and after blood collection for glucose evaluation, the livers were perfused and the glucose, urea, pyruvate and L-Lactate production from L-alanine were done. Finally, the retroperitoneal, epididimal and inguinal fat were removed and weighted. Mice which received HF diet showed fasting hyperglycemia and increased liver glucose production from L-alanine but these changes was prevented by the treatment with infliximabe. In contrast, mice treated with high sucrose diet during two, three or four weeks, in spite of the increased body weigh and retroperitoneal, epididimal and inguinal fat, did not show alteration in fasting glycemia or liver glucose, urea, pyruvate and L-Lactate production from L-alanine. The results open the possibility of using HL diet as a suitable model to study potential antidiabetic drugs with a potential role to promote reversibility of LGO in the diabetic and pre-diabetic condition.